Effect of social media marketing on traditional marketing campaigns in young Icelandic companies - Anna Guðbjörg Cowden 1989- (2014)
While marketing has traditionally been promoted through advertisements and campaigns, it is evident that the dawn of the social media age is changing the way that companies interact with their customers and market their products. In this study, seven different young Icelandic companies are interviewed through Individual Depth Interviews (IDI’s) to examine the role of social media within the company, and what effect, if any, it has on the company’s use of traditional marketing. The seven companies, Orthus Entertainment, Roadhouse, Ævi, Mindgames, Define the Line, Saffran, and GreenQloud, are all under five years old and participated in thorough interviews of their marketing practices based on five different roles: acquisition marketing, retention marketing, direct marketing, B2C marketing, and brand marketing. Through an in-depth analysis of the results, it is clear that social media marketing is used mainly for retention, with traditional marketing used for acquisition. Social media marketing also appeared to have a significant effect on the company’s traditional marketing campaign, as they mainly opted to utilize free traditional PR strategies to lobby for interviews and forgo other traditional marketing methods. Keywords: Social Media Marketing, Young Companies, Startups, Traditional Marketing, Iceland, Acquisition Marketing, Retention Marketing, Direct Marketing, B2C Marketing, Brand Marketing